Physiological and biochemical responses of Scenedesmus quadricauda exposed to copper ions - Silva, Jaqueline Carmo da (2018)
Copper is an important metal for industry, and its threshold in natural ecosystems has increased since the industrial revolution. As a micronutrient, it is required in minute amounts (~10-8 molL-1 Cu2+ ions), but can be toxic in concentrations above that, causing great biochemical transformations in microalgae. This study aimed at investigating the physiology of Scenedesmus quadricauda, a cosmopolitan species, exposed to copper concentrations including those that trigger intracellular biochemical modifications. It was divided in two parts, one to investigate the general physiology of the microalgae and the other to investigate the photosynthetic process. Copper concentrations ranged from 0.1 to 25 µM, thus including environmentally important levels. Microalgae cultures were kept under controlled environmental conditions and monitored daily for cell density, in vivo chlorophyll a, and photosynthetic quantum yield (ΦM). After 96 h Cu exposure, cellular Cu concentration, total carbohydrates, proteins and lipids were determined. The results showed that cellular copper and chlorophyll a per cell increased proportionally to Cu concentration in the culture medium and that microalgae cell density was mostly affected at 2.5 µM Cu and above. Approximately 31% decrease in quantum yield was obtained at the highest Cu concentration (25 µM) in comparison with the control, but at a concentration 10 times lower (2.5 µM Cu), the highest biomolecule yield was obtained for carbohydrates and proteins, but not for lipids. Results of the second part showed that the photosynthetic parameters, chlorophyll per cell volume, and viability decreased as a function of the copper added, whereas biovolume and chlorophyll a per cell increased. The present results suggest that at the range of Cu concentration tested, copper inhibited S. quadricauda cell division and significantly affected the photosynthetic process. This study is a contribution to the understanding of the effects of environmentally significant copper concentrations in the physiology of S. quadricauda.